THE EFFECTS OF PROPOSED TAX CHANGES ON POVERTY AND VULNERABLE GROUPS IN SERBIA - Matković, Gordana; Mijatović, Boško (Economic Annals, 2011)
This paper provides an empirical analysis of the potential effects of a proposed tax reform in Serbia on poverty and vulnerable groups. The essence of the proposal is transferring the tax burden from wages to personal consumption, thus alleviating one production factor and therefore stimulating economic growth. The analysis utilizes the tax-benefit microstimulation model, based on the Household Budget Survey for 2009. Since the model does not include the production sector, the estimated effects are direct, income-based, without the potential economic growth. As expected, the total personal consumption in Serbia would decrease (-3.4%), while poverty would increase (from 6.9 to 7.4%). All of the potentially vulnerable groups would be relatively equally affected. The conclusion is that it is questionable whether it is prudent to implement a tax reform during times of crisis and increased poverty that would probably result in negative short term social outcomes and whose long term effects are still unclear.